2.76–3.98 μm picosecond mid-infrared optical parametric generation in a muti-grating MgO: PPLN - Li, Bowen; Yin, Jinde; Wang, Jintao; Yang, Junbo; Yan, Peiguang (Frontiers in Physics, 2022)
The high repetition rate, widely tunable, picosecond mid-infrared laser plays an important role in various fields. In this paper, the single-pass optical parametric generator (OPG) pumped by Yb-fiber laser based on MgO: PPLN is proposed. The Yb-fiber laser is mode locked by a nonlinear amplifying loop mirror (NALM) with an all-polarization-maintaining (PM) structure. A maximum power of 6.2 W was obtained with a repetition rate of 15.8 MHz and pulse duration of 18 ps after amplification by cascaded fiber. Based on the principle of nonlinear frequency down-conversion, the tunable mid-infrared output wavelength of 2.76-3.98 μm was realized by varying the crystal grating periods and temperature. The maximum power was 500 mW at 3.22μm, corresponding to a quantum conversion efficiency of 25%, and the relative power fluctuation was measured as 0.37% over 30 mins.